2022
DOI: 10.1093/cdn/nzab154
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of High and Low Branched-Chain Fatty Acid–Producing Phenotypes in Holstein Cows following High-Forage and Low-Forage Diets in a Crossover Designed Trial

Abstract: Background Branched chain fatty acids (BCFA) are rumen-derived fatty acids comprising about 2% of bovine milk fatty acids. BCFA possess anti-inflammatory properties and enriching the BCFA content of bovine milk may provide human health benefits. Objective We determined whether forage content impacts the BCFA content of milk from Holstein cows and identified fatty acid phenotypes in high vs low BCFA-containing milks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In the present study, total BCFAs were not significantly different based on diet or breed, but individual BCFAs were higher in beef from GRASS. Information about BCFA content in beef is sparse in the literature, but Picklo et al [ 52 ] reported higher levels of BCFAs in beef from cattle fed a high-forage diet as compared to a low-forage diet. Klopatek et al [ 16 ] also stated that a 100% forage diet would result in higher amounts of BCFAs in beef compared to a standard grain-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, total BCFAs were not significantly different based on diet or breed, but individual BCFAs were higher in beef from GRASS. Information about BCFA content in beef is sparse in the literature, but Picklo et al [ 52 ] reported higher levels of BCFAs in beef from cattle fed a high-forage diet as compared to a low-forage diet. Klopatek et al [ 16 ] also stated that a 100% forage diet would result in higher amounts of BCFAs in beef compared to a standard grain-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…MOs were reported as abundance relative to the matching oligosaccharide internal standard. The MFAs are from the milk samples that Picklo et al reported earlier ( 58 ). Briefly, MFAs were measured from 0.1 mL of milk in duplicate for each collection day and reported as the mean value for each treatment in grams per 100 mL of milk.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, most of the genera associated with MFA, MO, or lactose abundances were not differentially abundant with diet (see Results). We did not include diet or parity in our models because diet and parity have been found to associate with MFAs ( 58 , 69 ), MOs ( 57 , 70 ), and lactose ( 71 ) in our cohort of cows and others; therefore, if diet and parity impact the milk microbes, then it may be through effects on the milk composition. With this reasoning, it would not be accurate to include diet and parity in our models as fixed effects completely independent of MFAs, MOs, or lactose.…”
Section: Methodsmentioning
confidence: 99%
“…Hexane (1 mL) was added followed by vortexing (30 s) and centrifugation (2000 g for 10 min at 4 °C). The hexane layer was removed, and the FAME profile was determined by GC–FID …”
Section: Methodsmentioning
confidence: 99%